2011
DOI: 10.2119/molmed.2011.00185
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Regional Brain Activation Patterns Assessed by Functional Magnetic Resonance Imaging in Patients with Systemic Lupus Erythematosus Stratified by Disease Duration

Abstract: The mediators of tissue damage in systemic lupus erythematosus (SLE) such as antibodies, cytokines and activated immune cells have direct access to most organs in the body but must penetrate the blood-brain barrier (BBB) to gain access to brain tissue. We hypothesized that compromise of the BBB occurs episodically such that the brain will acquire tissue damage slowly and not at the same rate as other organs. On the basis of these assumptions, we wished to determine if duration of disease correlated with brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 57 publications
4
36
0
Order By: Relevance
“…A summary of the studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) is depicted in Table 1. The largest original study contained 31 participants with SLE, whilst the smallest included 9 patients.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of the studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) is depicted in Table 1. The largest original study contained 31 participants with SLE, whilst the smallest included 9 patients.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
“…Mackay et al (14) had demonstrated a significant increase in neural activation in cortical areas associated with cognition during working memory task (cingulate gyrus, prefrontal cortex, somatomotor cortex and Brodmann area BA40, as well as the hippocampus, cingulated gyrus and prefrontal cortex in short-term SLE patients (< 2 years duration of SLE disease) in the absence of prior neuropsychiatric events or structural changes on brain MRI as compared to long-term SLE patients (> 10 years duration of disease). Furthermore, there was an increased activation in the amygdale and superior parietal regions in response to stimulation with unmasked neutral and fearful faces in the short-term SLE patients compared with the long-term SLE patients.…”
Section: Behavioral Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Although non-NPSLE patients do not manifest neuropsychiatric symptoms, neuroimaging studies have demonstrated some abnormalities in their brains. With regard to brain functions, functional magnetic resonance imaging (fMRI) researches reported some disruptions in several functional systems, such as working memory (Hou et al, 2013, Mackay et al, 2011), attention (Hou et al, 2013), learning memory (Shapira-Lichter et al, 2013), and language processing functional systems (DiFrancesco et al, 2007) in non-NPSLE patient groups. With regard to brain structure, the volume and thickness of gray matter show no abnormality in a non-NPSLE group (Jung et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of antibodies capable of altering the function of neuronal cells offers a promising avenue to study the diffuse CNS syndromes associated with NPSLE. Indeed, an increasing number of studies have strengthened the idea that some non-focal symptoms can be linked to the presence of DNRABs, a subclass of DNA-reactive antibodies that bind the GluN2A and GluN2B subunits of the n -methyl-d-as-partate receptor (NMDAR) with very high specificity and do not appear to bind any other brain molecule [3949]. There is now compelling evidence for the pathogenic role of DNRABs in NPSLE [5055] suggesting that these antibodies can cause more than one manifestation, specifically memory dysfunction and emotional disturbance, depending on the mechanisms by which DNRABs penetrate the blood–brain barrier (BBB) that separates the brain from circulation.…”
Section: Brain-reactive Antibodies In Npslementioning
confidence: 99%